2019
DOI: 10.3889/oamjms.2019.479
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CD4/CD8 Ratio with Carotid Intima-Media Layer Thickness in HIV/AIDS Patients at Sanglah General Hospital, Bali, Indonesia

Abstract: BACKGROUND: The discovery of antiretroviral (ARV) drugs in 1996 led to a shift in the causes of mortality and morbidity of patients with HIV/AIDS. Initially, the cause of mortality and morbidity was associated with opportunistic infection HIV/AIDS-related complication, but now are more associated with non-AIDS complication such as cardiovascular disease. Atherosclerosis is a major cause of cardiovascular disease. The atherosclerosis was assessed by measuring carotid intima-media thickness (CIMT) using B mode u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
4
0
3
Order By: Relevance
“…Regarding the relationship of IMT and immune status, we found a trend towards a lower CD4/CD8 ratio among patients with IMT ≥ 0.9 mm, although the difference did not reach statistical significance. Similar findings have been published previously 8 . Furthermore, we observed that patients with pathological IMT had a lower value of CD4 cells at the time of study inclusion.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the relationship of IMT and immune status, we found a trend towards a lower CD4/CD8 ratio among patients with IMT ≥ 0.9 mm, although the difference did not reach statistical significance. Similar findings have been published previously 8 . Furthermore, we observed that patients with pathological IMT had a lower value of CD4 cells at the time of study inclusion.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the relationship of the IMT and the immunological situation o, we found a tendency to a lower ratio of CD4/CD8 cells among patients with pathological IMT although without statistical signi cance. Similar ndings have been published [8]. In addition, in this study it was observed that patients who presented a pathological IMT had a lower value of CD4 cells at the time of study inclusion.…”
Section: Discussionsupporting
confidence: 91%
“…New analytical and radiological markers are being investigated in order to achieve an earlier diagnosis of atherosclerosis that will allow a more accurate selection of patients who need to perform a primary cardiovascular prophylaxis [6]. Among radiological tests to determinate subclinical atherosclerosis, carotid doppler ultrasound [7][8][9][10] for the measurement of mean intimate thickness (IMT) and coronary artery calcium score [11][12][13] are are the most studied ones in HIV-infected people.…”
Section: Introductionmentioning
confidence: 99%
“…different racial compositions, age ranges, treatment types) and a priori risk for cardiovascular disease [4,[17][18][19][20][21][22]. Lower CD4 þ /CD8 þ is associated with greater carotid artery intimal media thickness in people with well controlled HIV [23,24].…”
Section: Discussionmentioning
confidence: 99%